2014
DOI: 10.1111/jfbc.12102
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Alliin, Saccharide Contents and Antioxidant Activities of Black Garlic during Thermal Processing

Abstract: This study aimed to explore the alliin, saccharides, antioxidant and some other physicochemical changes of black garlic during the thermal processing steps. The contents of alliin and polysaccharides decreased significantly after 10 days of heat treatment, whereas the content of reducing sugars increased correspondingly. The 57.14% of fructose, 6.78% of glucose and 7.62% of sucrose were mainly saccharides in black garlic to answer for its sweet taste. The color value of black garlic increased over time, wherea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
78
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(86 citation statements)
references
References 30 publications
5
78
1
2
Order By: Relevance
“…The results showed that FGPS mainly contained fructose, galactose, and galacturonic acid at a mole ratio of 307:25:32, whereas BGPS was mainly composed by galactose and galacturonic acid at a molar ratio of 63:20. It is indicated in the previous report that, during the thermal process from fresh garlic to black garlic, polysaccharides were degraded to monosaccharides or oligosaccharides (Zhang and others ). Therefore, the results suggested that the fructan in black garlic was decomposed during the fermentation treatment, although the galactan was still intact and the galacturonic acid might come from the galactan after acid hydrolysis.…”
Section: Resultsmentioning
confidence: 98%
“…The results showed that FGPS mainly contained fructose, galactose, and galacturonic acid at a mole ratio of 307:25:32, whereas BGPS was mainly composed by galactose and galacturonic acid at a molar ratio of 63:20. It is indicated in the previous report that, during the thermal process from fresh garlic to black garlic, polysaccharides were degraded to monosaccharides or oligosaccharides (Zhang and others ). Therefore, the results suggested that the fructan in black garlic was decomposed during the fermentation treatment, although the galactan was still intact and the galacturonic acid might come from the galactan after acid hydrolysis.…”
Section: Resultsmentioning
confidence: 98%
“…The samples were extracted according to the literature with some modification (Joo and others ; Zhang and others ). The Amadori and Heyns compounds are easily dissolved in water; therefore, the samples were extracted with deionized water (Millipore, Bedford, Mass., U.S.A.).…”
Section: Methodsmentioning
confidence: 99%
“…Some studies reported that the 5‐HMF content in black garlic increased, the color of garlic extracts changed to black, and the pH value decreased from 7.46 to 3.93 (Li and others ; Liang and others ). In addition, some studies reported that the polysaccharides in black garlic were easily degraded into monosaccharides and oligosaccharides during the thermal processing of black garlic (Zhang and others ). Nevertheless, the analysis of the contents of fructan in black garlic and the key intermediates (Amadori and Heyns compounds) between raw garlic and black garlic have not yet been investigated in detail; it is important to analyze the Maillard reaction in black garlic to assess and control the quality of black garlic.…”
Section: Introductionmentioning
confidence: 99%
“…However, the expected time for allinase inactivation strongly depended on the heating method, temperature, heat transfer rate, when even a small amount of residual biologically active allinase may be able to hydrolyse ACSOs. Zhang et al (2015) demonstrated that garlic stored for 10 days at 70-80 °C showed a continuous decrease in alliin reaching a minimum after 4 days, with a significant drop in activity after the 2 days. It was postulated that Maillard reactions and degradation of alliin are potential explanations, where OSC (e.g.…”
Section: )mentioning
confidence: 97%
“…It has been shown that Allium containing vegetables, especially garlic, possess very high antioxidant activities (Halliwell et al, 1992;Kinalski and Noreña, 2014;Locatelli et al, 2017;Zhang et al, 2015), with various bioactivities such as antifungal (Fratianni et al, 2016;Li et al, 2014;Yoshida et al, 1987), antiviral (Weber et al, 1992), antibacterial (Brown et al, 2013;Yoshida et al, 1999), hypoglycemic (Liu et al, 2007;Ryan et al, 2001), hyperglycemic (Hou et al, 2010;Moradi et al, 2013), hypolipidemic (Bordia et al, 1998) and anti-atherosclerotic activities (Ashraf et al, 2005;Karagodin et al, 2016). Furthermore, recent studies have associated garlic consumption with preventive effects on human cancer (Chiavarini et al, 2016;de Giorgio and Stebbing, 2016;Kaschula et al, 2016;Myneni et al, 2016;Saud et al, 2016;Smith et al, 2016).…”
Section: Bioactivity Perspectives and Applications Of Allium Sulfur mentioning
confidence: 98%